Kreatywność językowa dzieci w wieku przedszkolnym - Szurek, Mateusz (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
Linguistic creativity is a form of children’s activity that involves the creation of new words not found in adult language. The period of specific speech is the moment of the most intensive development of vocabulary – this is the time of the final formation of the language system. The linguistic creativity and cognitive activity of preschool children has a significant impact on the increase in the number of new forms created by them, which are neologisms. In this article the author discusses the ways of creating neologisms and neosemantisms by children aged 3–6 years.